2008
DOI: 10.1016/j.bbamcr.2008.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle-dependent expression of Kv1.5 is involved in myoblast proliferation

Abstract: Voltage-dependent K(+) channels (Kv) are involved in the proliferation of many types of cells, but the mechanisms by which their activity is related to cell growth remain unclear. Kv antagonists inhibit the proliferation of mammalian cells, which is of physiological relevance in skeletal muscle. Although myofibres are terminally differentiated, some resident myoblasts may re-enter the cell cycle and proliferate. Here we report that the expression of Kv1.5 is cell-cycle dependent during myoblast proliferation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
68
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(71 citation statements)
references
References 41 publications
3
68
0
Order By: Relevance
“…In addition, Kv1.5 expression also increased in LMS. Both results are in agreement with previous reports demonstrating that Kv1.5 and Kv1.3 play a role in skeletal and smooth muscle cell proliferation (2,3,11).…”
Section: A B Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…In addition, Kv1.5 expression also increased in LMS. Both results are in agreement with previous reports demonstrating that Kv1.5 and Kv1.3 play a role in skeletal and smooth muscle cell proliferation (2,3,11).…”
Section: A B Discussionsupporting
confidence: 83%
“…Kv channels, which control cell excitability in muscle, also contribute to myoblast proliferation (2,11). In this study, we have shown for the first time that the expression of Kv1.3 and Kv1.5 increased in smooth muscle tumorigenesis in a close correlation with malignancy.…”
Section: A B Discussionmentioning
confidence: 60%
See 3 more Smart Citations